2013
DOI: 10.1016/j.neuroimage.2013.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sustained BOLD activation in the rat barrel cortex and neurochemical consequences

Abstract: To date, only a couple of functional MR spectroscopy (fMRS) studies were conducted in rats. Due to the low temporal resolution of 1 H MRS techniques, prolonged stimulation paradigms are necessary for investigating the metabolic outcome in the rat brain during functional challenge. However, sustained activation of cortical areas is usually difficult to obtain due to neural adaptation. Anesthesia, habituation, high variability of the basal state metabolite concentrations as well as low concentrations of the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
96
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(114 citation statements)
references
References 33 publications
(39 reference statements)
17
96
1
Order By: Relevance
“…channels in layer V of the barrel cortex (Nuñez et al 2012). Functional MR spectroscopic techniques have recently been translated to animals (Just et al 2013) and have demonstrated significant neurochemical changes (Glutamate and Lactate) in the rat barrel cortex during activation in accordance with previous results in the human cortex. We, therefore, truly believe that indirect mapping of calcium-dependent synaptic activity in cortical layers with quantitative AIM-MRI could help interpreting neurovascular and neurometabolic couplings in the cerebral cortex.…”
Section: Discussionsupporting
confidence: 73%
“…channels in layer V of the barrel cortex (Nuñez et al 2012). Functional MR spectroscopic techniques have recently been translated to animals (Just et al 2013) and have demonstrated significant neurochemical changes (Glutamate and Lactate) in the rat barrel cortex during activation in accordance with previous results in the human cortex. We, therefore, truly believe that indirect mapping of calcium-dependent synaptic activity in cortical layers with quantitative AIM-MRI could help interpreting neurovascular and neurometabolic couplings in the cerebral cortex.…”
Section: Discussionsupporting
confidence: 73%
“…This methodology can be used in both clinical settings (e.g., Prichard et al, 1991; Rothman et al, 1992; Gruetter et al, 1994, 1998a, 2001; Shen et al, 1999; Gruetter, 2002; Lebon et al, 2002; de Graaf et al, 2004; Mangia et al, 2007; Oz et al, 2007, 2015; Lin et al, 2012; Schaller et al, 2013, 2014; Bednařík et al, 2015) and pre-clinical studies (e.g., Mason et al, 1992; Hyder et al, 1996, 1997; Sibson et al, 1998, 2001; Choi et al, 2002; Henry et al, 2002; Patel et al, 2004, 2005a; Deelchand et al, 2009; Duarte and Gruetter, 2013; Duarte et al, 2011, 2015; Mishkovsky et al, 2012; Just et al, 2013; Bastiaansen et al, 2013, 2015; Lanz et al, 2014; Sonnay et al, 2015, 2016, 2017). However, in most animal applications it requires anesthesia, which can modify the coupling between neuronal activity, brain metabolism and vascular regulation of blood flow (Masamoto and Kanno, 2012; Sonnay et al, 2017, and references therein).…”
Section: Dynamic 13c Magnetic Resonance Spectroscopy (13c Mrs)mentioning
confidence: 99%
“…The main challenge associated with 1 H MRS is the complexity of the neurochemical profile composed of several overlapping metabolite signals on a relatively small frequency range (i.e., 4–5 ppm) that is to be analyzed (de Graaf, 1998). An extension of this technique is 1 H functional MRS (fMRS) that focuses on time-dependent changes in metabolite concentrations, which are associated with metabolic pathways during brain activity (Prichard et al, 1991; Mangia et al, 2007; Lin et al, 2012; Just et al, 2013; Schaller et al, 2013, 2014; Bednařík et al, 2015). The difficulty associated with the detection of small concentration changes occuring during neuronal activation can yet be overcome by using high magnetic field MR system (≥9.4 T) to increase spectral resolution and sensitivity.…”
Section: Dynamic 13c Magnetic Resonance Spectroscopy (13c Mrs)mentioning
confidence: 99%
“…Commonly, the sensitivity issue in functional 1 H-MRS studies in humans and rats is addressed by using 1 H single voxel spectroscopy (SVS) with relatively large voxels (typically 10-50 μl) to achieve a temporal resolution of several minutes (Hyder et al, 1996;Just et al, 2013;Xu et al, 2005). Localization in SVS techniques involves the formation of spin echoes, which is associated with significant signal loss due to T 2 relaxation compromising the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…While structural MRI is widely used in this context, functional neuroimaging in mice remains challenging: fMRI-based readouts assessing activity-induced hemodynamic changes in the blood oxygenation (BOLD) or cerebral blood volume (CBV) in mice appear to be dominated by systemic hemodynamic effects (Schroeter et al, 2014). Therefore, alternative readouts of brain function such as functional MRS, which is not based on cerebral hemodynamics and therefore should be less susceptible to systemic confounds, become highly attractive.Commonly, the sensitivity issue in functional 1 H-MRS studies in humans and rats is addressed by using 1 H single voxel spectroscopy (SVS) with relatively large voxels (typically 10-50 μl) to achieve a temporal resolution of several minutes (Hyder et al, 1996;Just et al, 2013;Xu et al, 2005). Localization in SVS techniques involves the formation of spin echoes, which is associated with significant signal loss due to T 2 relaxation compromising the sensitivity.…”
mentioning
confidence: 99%